Usulan Jadwal Perawatan Preventif Mesin HGF di Stasiun Puteran Pabrik Gula - Wahyudi Sutopo; Ari Nugroho; Yuniaristanto - (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2008)
The HGF (High Grade Fugal) Machine is one of the machines which often failed in The Sugar Factory XYZ. Brake Shoes and Belt drive are critical components of HGF Machine. The Management already used corrective maintenance policy where the maintenance only was done while the machines were failed. The loss of corrective maintenance was the other components which could be failed caused by failure of critical components. To anticipate this event could conduct the preventive action at critical components before the critical components reached limit usage. Considering was the situation above, this research concern how to arrange the appropriate preventive maintenance schedule, so that could be eliminate the failure frequency which caused by critical component failed. Time to failure of critical component is fitted the normal distribution with the test of hypothesis Kolmogorov-Smirnov. In analysis uses 70 % minimum reliability. The result shows the time to failure of Brake shoes and Belt drive havenormal distribution. The interval of preventive maintenance for belt drive of HGF WS machine is 28 days, and has the reliability value 73.8%, and for the Brake shoes of HGF WS machine is 28 days, and has the reliability value above 90%. The interval preventive maintenance for Brake shoes of HGF Zagitter machine is 20 days, and will be has reliability value 86,2%. The Interval of the preventive maintenance for the belt drive of HGF Zagitter machine is 24 days, and will be has reliability value above 90%.